Analysis of the influence of dienitro on co and nox emissions in diesel public transport buses with egr and scr systems (Tecno-Lógica, 2020)
Transport of people and goods has always been associated with the generation of some pollution, whether atmospheric, sound or visual. Managing the urban environment presents a major challenge: preserving environmental resources and also ensuring decent living conditions for the current population and for future generations. In the era of motorized and carbonized transport, vehicles are the main source of emission of atmospheric pollutants, mainly in large urban centers and important precursors of ozone. An important advance in minimizing vehicle emissions was the introduction of cleaner and additive fuels into the Brazilian market. The aim of this study was to evaluate the influence of the use of 0.15% dienitro on S50 Diesel in engines with EGR (Exhaust Gas Recirculation) and S10 Diesel in engines with SCR (Selective Catalytic Reduction) and EGR system. The tests were performed with a gas analyzer directly on the exhaust of vehicles with engine speed of 1300 rpm. Results show CO emission reductions of 72.8, 37.9, 15.7% and NOx emission reductions of 48.0, 48.5 and 31.0%, respectively for the S50 EGR, S10 SCR and S10 EGR system. This additive has a slight increase of 1 or 1.5 points in cetane number, low vaporization enthalpy (energy to vaporize) and high combustion enthalpy, ie, Dienitro increased cetane number, faciliting the start of combustion and reducing CO. On the other hand, a fuel that releases less energy during combustion consequently produces lower temperatures within the combustion chamber, ie additives with lower combustion enthalpy have lower NOx emissions.